The value of bedside teaching in undergraduate medical education: a literature review - Viswanathan Narayanan (MedEdPublish, 2020)
Background: Bedside teaching used to be an integral component of undergraduate medical education. In recent times, however, there has been a steady decline in the use of bedside teaching. This has occurred despite students, clinicians and patients viewing bedside teaching as valuable.